Squeezed microwave and magnonic frequency combs - A. Kani; M. Hatifi; J. Twamley (APL Quantum)
We present a theoretical framework for generating squeezed microwave and magnonic frequency combs achieved through the parametric coupling of magnon modes to a cavity. This coupling exploits the intrinsic non-linear magnon modes of a ferromagnetic sphere. When subjected to a strong, coherent microwave field, we show that the system exhibits spontaneous generation of squeezed frequency combs. Our exploration crosses various regimes of comb generation, prominently highlighting phenomena such as squeezing and squeezed lasing. This study paves the way for a pioneering room-temperature, multi-frequency maser characterized by both its magnonic and microwave squeezing properties. The implications of our findings hold promise for advancements in spintronics, quantum sensing, information processing, and quantum networking.